New Approach for Determination of Oxonium Ion in Inorganic Acids by Quenched Fluorescence of Analytically Interested Species via the Liberated Bromine Using Continuous Flow Injection Laser Diode Fluorimeter Analyser - Shakir, Issam; Hassan, Raed (Iraqi Journal of Science, 2025)
A new method is characterized by simplicity, accuracy and speed for determination of Oxonuim ion in ionisable inorganic acid such as hydrochloric (0.1 - 10) ,Sulphuric ( 0.1 - 6 ),nitric ( 0.1 - 10 ), perchloric ( 0.1 - 7 ), acetic (0.1 - 100 ) and phosphoric ( 0.1 - 30 ) ( mMol.L-1 )acids. By continuous flow injection analysis. The proposed method was based on generation of bromine from the Bro-3-Br– H3O+. Bromine reacts with fluorescein to quenches the fluorescence . A sample volume no.1 (31μl) and no.2 (35μl) were used with flow rate of 0.95 mL.min-1 using H2O line no.1as carrier stream and 1.3 mL.min-1 using fluorescein sodium salt line no.2. Linear regression of the concentration ( mMol.L-1 ) Vs quenched fluorescence gives a correlation coefficient of ( 89.33 -99.72 ) for all studies of acids in various parameters were optimized. The proposed method was applied successfully for the determination of Oxonium ion in commercial samples. Using paired t-test between the newly developed method and classical method; shows that there were no significant differences between either methods. On this basis the new method can be accepted as an alternative analytical method for determination of Oxonium ion in commercial samples.